Nomophobia, phubbing, and deficient sleep patterns in college students - Margit Julia Guerra Ayala; Olga María Alegre de la Rosa; Maria Amparo del Pilar Chambi Catacora; Elizabeth Vargas Onofre; Edith Cari Checa; Débora Díaz Flores (Frontiers in Education)
In the current context, excessive mobile device use has led to new issues, such as nomophobia—an irrational fear of being without a mobile phone—and phubbing, which involves ignoring nearby people in favor of using one’s phone. These behaviors are increasingly prevalent among young people, particularly in university settings, and can negatively impact well-being, including the emergence of poor sleep patterns. Given that sleep is essential for academic performance and mental health, examining how nomophobia and phubbing relate to disruptions in university students’ sleep habits is crucial. This study aimed to analyze the correlation between nomophobia, phubbing, and poor sleep patterns among university students, determine whether nomophobia and phubbing are significant predictors of these patterns, and examine the individual contribution of each variable on sleep. A non-experimental, cross-sectional, quantitative design with correlational-explanatory scope was used, conducted from March to June 2023. The sample consisted of 533 students from a private university in Peru, aged 18 to 24, selected through non-probabilistic sampling. Data were collected using the Short Nomophobia Questionnaire (SNQ-5) and the Brief Phubbing Scale (BPS-6), validated instruments with strong internal consistency. The results showed moderate positive correlations between nomophobia, phubbing, and poor sleep patterns. Linear regression analysis indicated that the predictor variables explained 45.1% of the variance in poor sleep patterns. Nomophobia significantly affected all three analyzed sleep patterns (late nights, insomnia, and short sleep), whereas phubbing significantly impacted only short sleep. The findings underscore the importance of addressing excessive mobile device use in university settings, as both nomophobia and phubbing affect students’ sleep quality. Future research is recommended to explore their impact on mental health and evaluate interventions to mitigate these phenomena and their implications for academic performance.